The Errors Found in Thesis Abstract Translations Made by English Department Students of UNP - Anisa Azhari; Havid Ardi (Universitas Negeri Padang, 2023)
Writing thesis abstracts in two languages, Indonesian and English, is one of the requirements for undergraduate students in Indonesia. Therefore, translation plays a significant role in exchanging information written in abstracts from Indonesian to English. This study aims to analyze the morpho-syntactic errors made by the fifth semester English education students of Universitas Negeri Padang. A descriptive research design was employed in this study. This study's population consisted of fifth semester English education students at Universitas Negeri Padang. The purposive sampling method was used to select 20 students as the sample. A translation test was used to collect data. The researcher analyzed and categorized the morpho-syntactic errors based on its types. Findings revealed that there were in total 196 morpho-syntactic errors found in students’ translation results. The most frequent type of error found is error in the use of articles, with a total amount of 63 data. Meanwhile, the least frequent type of errors is wrong sequence of tense, with a total amount of 2 data.